Prevalence of antimalaria drug resistance-conferring mutations associated with sulphadoxine-pyrimethamineine-resistant Plasmodium falciparum in East Africa: a systematic review and meta-analysis - Wagaw Abebe; Agenagnew Ashagre; Tadesse Misganaw; Zelalem Dejazmach; Getinet Kumie; Marye Nigatie; Abdu Jemal; Zelalem Asmare; Woldeteklehaymanot Kassahun; Solomon Gedfie; Ermias Getachew; Muluken Gashaw; et al. (Annals of Clinical Microbiology and Antimicrobials)
Abstract Background The emergence and spread of drug resistance to antimalarial drugs pose a severe threat to effective malaria control and treatment. Although sulfadoxine-pyrimethamine resistance is well-documented, it is still the drug of choice for treating intermittent resistance. Molecular markers play a crucial role in tracking and understanding the prevalence of antimalarial drug resistance. Currently, there is insufficient information on the prevalence of molecular markers associated with sulfadoxine-pyrimethamine resistance in P. falciparum. Objective This systematic review and meta-analysis aimed to determine the pooled prevalence of antimalaria drug resistance-conferring markers associated with sulphadoxine-pyrimethamineine in Plasmodium falciparum in East Africa. Methods Systematic searche was performed to retrieve articles from PubMed, Scopus, Science Direct databases, and Google Scholar search engine. Sixteen potential studies that provided important data on markers for sulphadoxine-pyrimethamineine resistance in Plasmodium falciparum were systematically reviewed and analyzed. Nine antimalarial drug resistance markers responsible for sulphadoxine-pyrimethamineine resistance in Plasmodium falciparum were extracted separately into Microsoft Excel and analyzed using STATA 17.0. The inverse of variance was done to evaluate heterogeneity across studies. A funnel plot was used to determine the presence of publication bias. A trim-and-fill-meta-analysis was carried out to generate a bias-adjusted effect estimate. A random effect model was used to determine the pooled prevalence of markers responsible for sulphadoxine-pyrimethamineine resistance. Subgroup analysis was performed based on country and year of publication. Results A total of 16 studies were included for this systematic review and meta-analysis.The molecular markers like dhfr (N51I, C59R, S108N, 108N, 59R, and I164L), and dhps (A437G, K540E, & 540E) were selected for meta-analysis. From this meta-analysis, the pooled prevalence of dhfr N51I, dhfr C59R, dhfr S108N, dhfr 108N, dhfr 59R, and dhfr I164L was 88.6%, 85.3%, 89.6%, 92.2%, 71.5%, and 3.9%, respectively. Likewise, the aggregated prevalence of dhps A437G, dhps K540E, and dhps 540E was 90.2%, 80.9%, and 91.5%, respectively. The subgroup analysis based on year of publication showed that the pooled prevalence of dhfr N51I, dhfr C59R, dhfr S108N, dhps A437G, and dhps K540E, in studies conducted 2014–2018 was 97.11%, 90.57%, 96.45%, 90.89%, and 89.45%, respectively, while it was 82.03%, 81.78%, 85.12%, 89.24%, and 73.98%, respectively, in studies conducted 2019–2023. On the other hand, country-based analysis showed that the pooled prevalence of dhfr N51I, dhfr C59R, dhfr S108N, dhps A437G, and dhps K540E, in Kenya was 85.88%, 84.02%, 86.56%, 90.7%, and 77.55%, respectively. Conclusions This systematic review and meta-analysis reveal a high prevalence of drug resistance markers  associated with sulphadoxine-pyrimethamine resistance in Plasmodium falciparum across the East African region. This underscores the significant challenges in managing malaria infections caused by Plasmodium falciparum in the region. Therefore, regular monitoring, identification, and limiting of drug-resistance markers and drug-resistant P. falciparum strains must be sustained to ensure the effectiveness of malaria treatment.